Moral Education for Parents in the Perspective of the Qur'an: Study of Surah Luqman Verses 14-15 - Dwi Alyanti; Rosdialena (Konsultan Jurnal Ilmiah Indonesia, 2026)
Moral education toward parents is one of the fundamental teachings in Islam that plays an important role in shaping children's character and personality. However, the development of modern lifestyles and social changes has led to a decline in the practice of respect and devotion toward parents. This study aims to analyze the concept of moral education toward parents from the perspective of the Qur’an through an examination of Surah Luqman verses 14–15, as well as to identify the educational values contained within these verses and their relevance to daily life. This study employed a qualitative library research method using the Qur’an, Qur’anic exegesis books, scholarly journals, and relevant literature as primary sources. The findings reveal that Surah Luqman verses 14–15 contain essential moral education values, including gratitude to Allah and parents, birr al-walidayn (devotion to parents), proportional obedience, patience, empathy, and maintaining good relationships with parents under all circumstances. Furthermore, these verses emphasize the importance of appreciating the sacrifices made by parents, particularly mothers, while affirming that obedience to parents must not contradict the principle of tawhid (the oneness of Allah). Therefore, the values embedded in Surah Luqman verses 14–15 remain highly relevant as a foundation for developing noble character and responsible behavior in family and social life.